Is capitalism compatible with democracy? - Wolfgang Merkel (Zeitschrift für Vergleichende Politikwissenschaft, 2014)
Capitalism and democracy follow different logics: unequally distributed property rights on the one hand, equal civic and political rights on the other; profit-oriented trade within capitalism in contrast to the search for the common good within democracy; debate, compromise and majority decision-making within democratic politics versus hierarchical decision-making by managers and capital owners. Capitalism is not democratic, democracy not capitalist. During the first postwar decades, tensions between the two were moderated through the socio-political embedding of capitalism by an interventionist tax and welfare state. Yet, the financialization of capitalism since the 1980s has broken the precarious capitalist-democratic compromise. Socioeconomic inequality has risen continuously and has transformed directly into political inequality. The lower third of developed societies has retreated silently from political participation; thus its preferences are less represented in parliament and government. Deregulated and globalized markets have seriously inhibited the ability of democratic governments to govern. If these challenges are not met with democratic and economic reforms, democracy may slowly transform into an oligarchy, formally legitimized by general elections. It is not the crisis of capitalism that challenges democracy, but its neoliberal triumph. During the first postwar decades, tensions between the two were moderated through the socio-political embedding of capitalism by an interventionist tax and welfare state. Yet, the financialization of capitalism since the 1980s has broken the precarious capitalist-democratic compromise. Socioeconomic inequality has risen continuously and has transformed directly into political inequality. The lower third of developed societies has retreated silently from political participation; thus its preferences are less represented in parliament and government. Deregulated and globalized markets have seriously inhibited the ability of democratic governments to govern. If these challenges are not met with democratic and economic reforms, democracy may slowly transform into an oligarchy, formally legitimized by general elections. It is not the crisis of capitalism that challenges democracy, but its neoliberal triumph. – – Kapitalismus und Demokratie folgen unterschiedlichen Logiken. Ersterer basiert auf Eigentumsrechten, individueller Gewinnmaximierung, hierarchischen Entscheidungsstrukturen und ungleichen Besitzverhältnissen, Letztere gründet auf der Suche nach Allgemeinwohl, Diskurs, politischer Gleichheit und den Verfahren konsensueller oder majoritärer Entscheidungsfindung. Kapitalismus ist nicht demokratisch und Demokratie nicht kapitalistisch. Während der ersten Nachkriegsjahrzehnte wurden die Spannungen zwischen Kapitalismus und Demokratie durch einen interventionistischen Steuer- und Wohlfahrtsstaat in Grenzen gehalten. Die Finanzialisierung des Kapitalismus seit den späten 1980er Jahren hat den prekären Kompromiss zerbrochen. Die kontinuierlich zunehmende sozioökonomische Ungleichheit übersetzt sich direkt in politische Ungleichheit. Das untere Drittel der Gesellschaft steigt schweigend aus der politischen Partizipation aus. Gleichzeitig haben Deregulierung und Globalisierung die Handlungsmöglichkeiten demokratischer Regierungen erheblich eingeschränkt. Dies sind gravierende Herausforderungen der Demokratie. Werden sie nicht ernst genommen und wird ihnen nicht mit wirtschaftlichen und politischen Reformen begegnet, werden sich die oligarchischen Tendenzen in Wirtschaft und Demokratie tiefer eingraben. Es ist nicht die Krise, sondern der Triumph des Kapitalismus, der die Demokratie in Bedrängnis gebracht hat.
Keywords: 320; Capitalism; Neoliberalism; Democracy; Rising inequality; Disembedding of capitalism; Financialization; Oligarchic trends; Marginalization of the lower strata